Pendampingan Implementasi Metode Muhafadzoh Dalam Pembelajaran Qowa’id Shorfiyyah Pada Santri Madin Assunniyyah Al Jauhari Kencong Jember - bin Nafsah, Nor Holis; Sholehudin, Moch. In (Universitas Al-Falah As-Sunniyah Kencong Jember, 2023)
In order to achieve the target of a lesson, it is necessary to have a correct and effective strategy and method, especially in applying learning in the digital era which is very influential in the low demand for student learning. One of these methods is the muhafadzoh method. In this research, the process of assisting the implementation of the Muhafadzoh method in learning Qowa'id Shorfiyyah will be examined for students at Madrasah Diinyyah Assunniyyah Al Jauhari Kencong Jember who have the ability to memorize Sharaf rules and learning motivation is still relatively low. It is hoped that with the implementation of this method, it can improve the ability to memorize and understand qowa'id shorfiyyah, as well as increase students' learning motivation. The methods used during the activity were Exploration, Creat and Action, Evaluation, and Report and Desimination. The conclusion from this dedication is that the Muhafadzoh method is very influential in increasing the ability to memorize, understand and study motivation of Santri Madrasah diniyyah Assunniyyah Al Jauhari Kencong Jember.